2017
DOI: 10.1007/s11249-017-0888-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of Permanent Shear Thinning of VM Polymer Solutions

Abstract: The ultrashear viscometer (USV) has been adapted and employed to investigate the permanent shear thinning of polystyrene solutions in a series of phthalate ester base fluids. The permanent shear stability index based on viscosities measured at 10 6 s -1 , PSSI(10 6 ), has been found to be a convenient way to express the magnitude of permanent shear thinning. When comparing permanent shear thinning at various shear rates in the USV, it is very important to take account of the different times of shear that are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
(76 reference statements)
0
18
0
Order By: Relevance
“…Then, in the 1940s it was found that very high molecular weight (MW) polymers in solution could show such chain rupture when subjected to high shear rates, resulting in permanent viscosity loss and limiting the molecular weight of polymers that could be used in lubricants [121]. A short review of permanent viscosity loss of viscosity modifiers has recently been provided by Marx et al [122], while a general review of the research on the mechanochemistry of polymers up to the late 1980s is given by Sohma [123]. In 1940 Kauzmann and Eyring, at the end of their paper on polymer viscosity, suggested that one mechanism of shear thinning was rupture of polymers caused by cleavage of their backbone C-C bonds due to mechanical force [14].…”
Section: Mechanochemistry In Tribology: Polymer Degradationmentioning
confidence: 99%
“…Then, in the 1940s it was found that very high molecular weight (MW) polymers in solution could show such chain rupture when subjected to high shear rates, resulting in permanent viscosity loss and limiting the molecular weight of polymers that could be used in lubricants [121]. A short review of permanent viscosity loss of viscosity modifiers has recently been provided by Marx et al [122], while a general review of the research on the mechanochemistry of polymers up to the late 1980s is given by Sohma [123]. In 1940 Kauzmann and Eyring, at the end of their paper on polymer viscosity, suggested that one mechanism of shear thinning was rupture of polymers caused by cleavage of their backbone C-C bonds due to mechanical force [14].…”
Section: Mechanochemistry In Tribology: Polymer Degradationmentioning
confidence: 99%
“…where KV base is the kinetic viscosity of the base oil at 100°C. A recent study suggested that PSSI may be a better way to describe permanent viscosity loss because it could, under some conditions, be related theoretically to polymer concentration and molecular weight [18]. [15].…”
Section: Shear Stabilitymentioning
confidence: 99%
“…In practice most engine oil VMs show such breakdown at shear rates above 10 6 s −1 , so that successive viscosity measurements made on the same sample at high shear rate show a progressive reduction in viscosity as permanent shear thinning accumulates. This phenomenon can be utilised to study the permanent shear thinning of polymer solutions [13]. To address this problem in the current study, a new polymer sample was used for each combination of shear rate and temperature by flushing the previously used sample 10 times with fresh polymer solution.…”
Section: High Shear Rate Viscosity Measurement (5 × 10 5 To 10 7 S −1 )mentioning
confidence: 99%
“…24. It is evident that all fit the data quite closely so it is thus not possible to use the data measured in (13)…”
Section: Alternative Shear Thinning Equationsmentioning
confidence: 99%